2019
DOI: 10.1017/jfm.2019.665
|View full text |Cite
|
Sign up to set email alerts
|

Breakup and non-coalescence mechanism of aqueous droplets suspended in castor oil under electric field

Abstract: The effect of an electric field on the coalescence of two water droplets suspended in an insulating oil (castor oil) in the non-coalescence regime is investigated. Unlike the immediate breakup of the bridge, as reported in earlier studies, e.g. Ristenpart et al. (Nature, vol. 461 (7262), 2009, pp. 377–380), the non-coalescence observed in our experiments indicate that at strong fields the droplets exhibit a tendency to coalesce, the intervening bridge thickens whereafter the bridge dramatically begins to thin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…Roy et al further numerically showed that the curvatures of the bridge influenced the bridge pressure in the applied electric field. [203] The critical cone angle separating the bouncing phase and coalescence phase is highly dependent on the viscosity of the liquid surrounding droplets. [204] The bouncing-off phenomenon between the oppositely charged droplets is also ubiquitous in many kinds of liquid combinations, like water and silicone oil, brine and crude oil, water and air etc.…”
Section: Oppositely Charged Dropletsmentioning
confidence: 99%
“…Roy et al further numerically showed that the curvatures of the bridge influenced the bridge pressure in the applied electric field. [203] The critical cone angle separating the bouncing phase and coalescence phase is highly dependent on the viscosity of the liquid surrounding droplets. [204] The bouncing-off phenomenon between the oppositely charged droplets is also ubiquitous in many kinds of liquid combinations, like water and silicone oil, brine and crude oil, water and air etc.…”
Section: Oppositely Charged Dropletsmentioning
confidence: 99%
“…2019) and mainly focused on the near-contact interaction preceding electrocoalescence (Anand et al. 2019; Roy, Anand & Thaokar 2019). The dynamics of drop approach and interactions at arbitrary separations has been considered mainly in the case of droplet pairs aligned with the electric field (Sozou 1975; Baygents, Rivette & Stone 1998; Lin, Skjetne & Carlson 2012; Mhatre, Deshmukh & Thaokar 2015; Zabarankin 2020), because the axial symmetry greatly simplifies the calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The two droplets approach each other and then directly contact for the first time to form liquid bridge ( t = 24 ms). After the contact, the electric charges inside two droplets are transferred through the liquid bridge and the direction of electric force is reversed 28 . The electric force tends to pull apart two droplets and break the liquid bridge.…”
Section: Resultsmentioning
confidence: 99%